The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1471-2148-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the genus Tarentola (Gekkota: Phyllodactylidae) from the Mediterranean Basin, estimated using multilocus sequence data

Abstract: BackgroundThe pronounced morphological conservatism within Tarentola geckos contrasted with a high genetic variation in North Africa, has led to the hypothesis that this group could represent a cryptic species complex, a challenging system to study especially when trying to define distinct evolutionary entities and address biogeographic hypotheses. In the present work we have re-examined the phylogenetic and phylogeographic relationships between and within all Mediterranean species of Tarentola, placing the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 51 publications
(94 reference statements)
3
74
1
Order By: Relevance
“…Resistance to dehydration is often associated with successful colonizers (e.g., Jeschke and Strayer 2008;Chown et al 2010;Kolbe et al 2010Kolbe et al , 2014. In contrast with these examples, the European lineage of T. mauritanica, which has been widely introduced across the Mediterranean basin (Rato et al 2010(Rato et al , 2012, has higher evaporative WL than the Iberian lineage regardless of body size. However, it must be taken into account that the recent human-mediated expansion of T. mauritanica has been directed toward northern and, hence, more humid areas than the central Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Resistance to dehydration is often associated with successful colonizers (e.g., Jeschke and Strayer 2008;Chown et al 2010;Kolbe et al 2010Kolbe et al , 2014. In contrast with these examples, the European lineage of T. mauritanica, which has been widely introduced across the Mediterranean basin (Rato et al 2010(Rato et al , 2012, has higher evaporative WL than the Iberian lineage regardless of body size. However, it must be taken into account that the recent human-mediated expansion of T. mauritanica has been directed toward northern and, hence, more humid areas than the central Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 93%
“…Molecular studies have gradually uncovered the extreme evolutionary diversity within T. mauritanica, with six identified lineages to date, suggesting that this taxon is, in fact, a complex of several species deserving specific status (Harris et al 2004a(Harris et al , 2004bPerera and Harris 2008;Rato et al 2010Rato et al , 2012. In the Iberian Peninsula, a temperate region of southern Europe that encompasses a high diversity of landscapes and climate regimes (Sillero et al 2009), two distinct mitochondrial lineages of the complex with parapatric distribution are found: an endemic clade distributed in central and southwestern Iberia (Perera and Harris 2008), hereafter called the Iberian clade, and the European clade, which occurs along the Iberian coastline (Rato et al 2012). This latter clade has a widespread distribution across southern Europe (from the Iberian Peninsula to Greece), including many Mediterranean islands, as a result of multiple introductions.…”
Section: Introductionmentioning
confidence: 97%
“…Barata, Carranza and Harris, 2012). Geckos in general seem to be a good example of this, as studies of Tarentola (Rato, Carranza and Harris, 2012) and Quedenfeldtia indicated possible cryptic species. Other species such as Saurodactylus brosseti also present extremely high mtDNA variability (Rato and Harris, 2008), although the lack of clear geographical structure of genetic variation precludes conclusions about cryptic species.…”
Section: Discussionmentioning
confidence: 94%
“…Zangad, Cimmaruta and Nascetti, 2006;Recuero et al, 2007). This is particularly true for geckos from the region; of studies from Morocco for example, all speeies analysed have included deeply divergent mtDNA lineages, at a level that could be considered cryptic species (Perera and Harris, 2010; Rato, Carranza and Harris, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…In North Africa, new cryptic diversity has recently been described in several taxa such as plants (Abdelaziz et al 2011), spiders (Duncan et al 2010), mammals (Ben Faleh et al 2012) and reptiles Rato et al 2012). The diverse geographical and geological features and the variety of climates exert different selective pressures that have promoted speciation processes in the region, and some areas, such as the Atlas Mountains, are especially interesting.…”
Section: Introductionmentioning
confidence: 99%